Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Matic Honda Pada PT. Honda bintang kharisma jaya Di makassar - Purnama Alam, Andi Rifqah; Suardi, Wisda Zulaeha; Muh Haerul (STIM-LPI Makassar, 2024)
The purpose of this research is to determine the influence of product quality on purchasing decisions for Honda automatic motorbikes at PT. Honda Bintang Kharisma Jaya in Makassar. The type of data used in this research is quantitative data. The data source used is primary data. The data analysis method used is descriptive questionnaire answers using a Likert scale and statistical analysis in the form of simple regression analysis, correlation coefficient, coefficient of determination, and t-test. The research results show that Y = 23.73 + 0.451, the coefficient of determination is r² = 0.5372 (53.72%), the correlation coefficient is r = 0.733. From the results of these calculations it shows that product quality has a positive and significant effect on the decision to purchase a bicycle Honda automatic motorbike at PT. Honda Bintang Kharisma Jaya in Makassar.